Writing Instruction in U.S. Colleges and Schools: The Twentieth Century and the New Millennium - Gold, David; Hammond, J. W. (A Short History of Writing Instruction, 2020)
Writing instruction has long been a central feature of U.S. education, and it has likewise long been a site of contest. For over a century, writing instructors have engaged in vigorous debate over the purpose of writing instruction: what should students write about and to what ends? Some have advocated for writing about social issues to prepare students for citizenship in a democracy; others for drawing on personal themes to promote students' growth as individuals; others for writing about literary texts as a means of enculturation; others for writing that would serve students' vocational and professional ends. While these views are not completely incompatible, they have vied for dominance at various times, shaping curricular decisions that have affected millions of students. In this chapter, we trace the development of writing instruction in U.S. colleges and schools from 1900 to 2020, paying attention to both pedagogical innovations and the social, economic, and technological forces that have shaped them.